Relevansi Open Educational Resources (E-Book) dalam Penghematan Finansial Mahasiswa - ., Dea Aulia Cintiaraa; ., Aufa Assa Syahada; ., Arrinda Windiana Nurfazhari S; ., Fariz Nurul Majdudin (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This study focuses on the role of Open Educational Resources (OER), specifically e-books, in student education. With the rapid development of technology, educational institutions are expected to keep up with the advancements in order to provide quality learning experiences. OER, including e-books, are freely available resources that offer cost-saving benefits to students. By accessing OER, students can save money that would have been spent on textbooks and other learning materials. This is particularly beneficial for financially disadvantaged students who may struggle to afford expensive textbooks. Additionally, OER availability can help bridge the educational gap between students from different backgrounds, ensuring equal access to educational resources. The study adopts a qualitative approach, utilizing observation, interviews, and documentation as data collection techniques. Through interviews with respondents, it was found that OER, especially e-books, are highly relevant in terms of student financial savings. By reducing the cost of textbooks and learning materials, students can save money and access quality learning materials on par with their peers. Overall, OER plays a significant role in minimizing financial burdens and promoting equitable education for all students.